KONTRIBUSI GAYA KEPEMIMPINAN DAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALITAS GURU DI SEKOLAH DASAR - Asri Darwanti; Sri Wahyuni; Azminudin Latif; Anam Sutopo; Sabar Narimo (STKIP Subang, 2024)
This study aims to describe the contributions of leadership and supervision by the school principal in enhancing the professionalism of elementary school teachers. This research employs a qualitative approach with a case study design. The subjects of this study are the principal and teachers of SDN 01 Wonokeling, Jatiyoso, Karanganyar. Data were collected through several techniques, including in-depth interviews, observations, and documentation. The data obtained were analyzed qualitatively using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The leadership style of the principal at SDN 01 Wonokeling, Jatiyoso, Karanganyar in enhancing teacher professionalism is democratic, where the leader views teachers as partners who can contribute, is open to suggestions and criticism, and fosters a harmonious working team. The principal's supervision in enhancing teacher professionalism is collaborative, where the principal and teachers share responsibilities and provide suggestions and ideas to improve teacher professionalism and education quality.